The Effect of Dividend Policy on Changes in the Stock Value of Banking Companies in the IDX30 Index in 2022 - Ghiffari, Faisal; Rohmat, Rohmat; Uzliawati , Lia (International Journal of Economics Studies, 2024)
This research aims to examine the relationship between dividend policy and stock prices. The population used consists of banking companies included in the IDX30 index from 2020 to 2022. The reason for choosing these companies is that the companies listed in this index tend to distribute dividends and have high trading liquidity. We collected data from banking companies that were part of the IDX30 during the period from 2020 to 2022. Multiple Linear Regression Analysis was used as the hypothesis testing technique. The results demonstrate that dividend policy positively impacts stock prices, and profitability, proxied by ROA, also positively influences the company's stock price.